Des morts polysémiques : les sépultures en contexte d’habitat rural au premier Moyen Âge (ve-xie siècle) en Alsace - Édith Peytremann; Amélie Pelissier (Archéologie Médiévale)
Abstract: Conducted as part of a Collective Research Project (PCR, Projet Collectif de Recherche) titled “Funerary spaces and practices in Alsace during Merovingian and Carolingian times”, the study of residential graves, discovered in early medieval rural dwelling contexts, aims to develop an archaeological and anthropological methodology that can be adapted to a heterogeneous corpus and limited research time, to analyse and compare the corpus from Alsace to other regional funerary groups as well as residential burial groups in other French regions and neighbouring German region of Bade-Württemberg. With a corpus of 171 burials and 192 individuals from 19 sites, 46 of which have been radiocarbon dated and 30 dated by typochronology of the artefacts, the project led to the development of a methodology allowing a chronological, topographical, proxemical, biological and social approach of the practice. Three chronological phases have been identified during the three centuries of the practice, as well as three topographical layouts of the burials: isolated, scattered, and grouped. Funerary gestures and architecture are similar to what is known for contemporary large burial groups. The demographic and biological study of the buried population gave similar results to data in cemeteries. Considering the characteristics and their limits, the family groups and beliefs, the interpretations proposed by this study are compared to what is known in France and North-Western Europe. These first results are modest, but this new methodology should help process other heterogeneous regional bodies of data and allow more precise comparisons.